The assistant referees' activity in refereeing elite football: Preoccupations when not judging offside. (May 2020) - Boyer, Simon; MacMahon, Clare; Récopé, Michel; Rix-Lièvre, Géraldine
Abstract: Objective: The purpose of this research was to study the preoccupations assistant referees had to participate in decision making about duels during football games. Design: Research adopted a phenomenological framework to investigate the assistant referees' lived experiences in order to understand their activity when they judged duels in match. Method: This study investigated six professional football matches. Researchers conducted a participatory observation of the refereeing team before each match. Twelve self-confrontation interviews with each assistant referee of each match were conducted in order to make him/her describing his/her unfolding lived experience during the match. Results: In case of players' duels, the perception of contextual cues enabled the assistants to appraise the occurring of a decision process with the central referee. For the assistants, the occurring of a decision process with the central referee meant his priority to intervene in the adjudication of duels, while the absence of decision process with the central referee meant for the assistants the possibility to intervene. The assistants adjusted their way of judging duels to how the central referee judged the previous ones. Conclusions: The participation of assistants in decision making about duels depends on their preoccupations concerning the central referee's priority. The way assistants perceive the central referee's contextual judgment shapes the way they adjudicate duels. A latent intention to coordinate with the central referee, in relation with their collaborative tasks, is embedded in their preoccupations. Our results are a platform to develop further research about the referees' collective activity. Highlights: Assistants have other preoccupations than judging off-side during the match. Assistants identify contextual cues to intervene in the refereeing of duels. Assistants have preoccupation with the central referee's priority to make decision. Assistants appraise whether there is a decision process happening with the referee. Assistants adjust their way of judging duels to how the central referee judges.